Analisis pengendalian persediaan bahan baku foot step menggunakan metode Economic Order Quantity (EOQ) pada CV Anugerah Teknik - Christoper, Djoshi William; Pangastuti, Nova; Parningotan, Sepriandi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
This study aims to determine whether inventory control of foot step raw materials with the Economic Order Quantity (EOQ) method is more efficient than the conventional method used by CV Anugerah Teknik. This research involves the calculation and comparison of the amount and frequency of ordering foot step raw materials. Data was collected through field and literature studies. The results showed that the frequency of ordering with the conventional method was 6 times with an average of 2,100 kg per order, while the EOQ method suggested 3 times with an average of 1,698 kg per order. CV Anugerah Teknik has not determined the safety stock, while the EOQ method recommends 514 kg. The reorder point applied by CV Anugerah Teknik is 2,000 kg, while the EOQ method recommends 2,032 kg. In 2022, the total cost of inventory with the EOQ method is lower at Rp 1,518,484,129 compared to the conventional method of Rp 1,760,469,931. In conclusion, inventory control of foot step raw materials is more optimal with the EOQ method than the conventional method applied by CV Anugerah Teknik.